Implikasi Pemikiran Kristologi Logos dalam Bingkai Perspektif Teologi Proses terhadap Relasi Antar Agama (Indonesian Journal of Theology, 2015)
The fact that religious plurality has become a growing reality, especially in Indonesia, demands that every religion and their respective adherents reconsider basic doctrinal premises that stand in dismissive exclusivity toward other religions. The doctrine of Christology appears as one of Christianity’s frequently claimed bases, in support of the notion of Christianity’s superiority to other religions. One such Christology is that of “Logos Christology,” as developed in the prologue of John’s Gospel (John 1:1-18). In order to understand Christology in a more inclusive way, a deeper contextual consideration of the Johannine prologue also invites its reinterpretation from different perspectives. In this essay, I attempt to demonstrate the suitability of process theology for the task of a more inclusive conception of Logos Christology—one in which aspects of the process and of relation, rather than of substance, become most fundamental for comprehension of reality.